Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/23802359.2018.1501309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome of summer snowflake (Leucojum aestivum, Amaryllidaceae)

Abstract: Leucojum aestivum (Amaryllidaceae) is an important medicinal plant native to Europe, North Africa, and Central Asia. Its wild resources are Endangered because of excavation. In the present study, the chloroplast genome of L. aestivum was sequenced. The plastome length is 157,241 bp. A total of 132 genes were identified, consisting of 86 protein-coding genes, eight rRNA genes, and 38 tRNA genes. Thirtyfour species from Asparagales were used for phylogenomic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[43][44][45][46] Studies have shown that alkaloid synthesis is dominated by the plant genotype, the activity of biosynthetic activities. [47][48][49][50][51][52] At present, there are three methods to produce galanthamine on a large scale vizcomplete chemical synthesis and extraction from field plants (e.g., Narcissus tazetta L. var. chinensis Roem., L. aestivum, Lycorisradiata var.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%
“…[43][44][45][46] Studies have shown that alkaloid synthesis is dominated by the plant genotype, the activity of biosynthetic activities. [47][48][49][50][51][52] At present, there are three methods to produce galanthamine on a large scale vizcomplete chemical synthesis and extraction from field plants (e.g., Narcissus tazetta L. var. chinensis Roem., L. aestivum, Lycorisradiata var.…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%